Consuming spicy food and type 2 diabetes incidence in Southwestern Chinese aged 30–79: a prospective cohort study - Liling Chen; Xiaomin Wu; Rui Zhang; Wenge Tang; Yuxuan Chen; Xianbin Ding; Jing Wu (Nutrition Journal)
Abstract Background Capsaicin is the main component of chili peppers and is believed to have antidiabetic effects. However, the association between spicy food consumption and the incidence of diabetes remains unclear. Methods A cohort of 20,490 Han residents aged 30–79 without diabetes at baseline were followed from enrollment to June 2, 2023. The consumption of spicy food was obtained through face-to-face surveys conducted during the baseline survey from October 2018 to February 2019. The definition of type 2 diabetes onset was based on the ICD-10 code of E11 in the diabetes case reporting system and death system; Additionally, self-reported diagnosis of diabetes by a physician in active follow-ups, or a fasting blood glucose level of ≥ 7 mmol/L or a glycated hemoglobin percentage of ≥ 6.5% found on-site during the resurvey. Both Cox proportional hazard regression and competing risk regression were used to calculate hazard ratios (HRs) and confidence intervals (CIs). Results During the follow-up period (53.5 ± 3.0 months), 182 individuals (1.1%) were newly diagnosed with T2D with an incidence rate of 246.2 per 100,000 person-years. Cox regression analyses revealed that spicy food consumers had a 34% reduced risk of developing type 2 diabetes (HR: 0.66, 95% CI: 0.48, 0.91) compared to non-consumers. The HRs (95% CIs) for participants consuming spicy food 3–5 days/week, 6–7 days/week, and with weak pungency were 0.45 (95% CI: 0.25, 0.81), 0.69 (0.49, 0.98), and 0.64 (0.46, 0.90), respectively. However, little significant protective effect was observed among those who consumed spicy food for 1–2 days/week, with moderate pungency, or with strong pungency (all P > 0.05). Conclusions Consuming spicy food may lower the risk of developing type 2 diabetes, particularly at a frequency of 3–5 days/week, and with weak pungency. Further multicenter prospective studies or interventional studies are needed to confirm these findings.